Functionalized BODIPYs as Fluorescent Molecular Rotors for Viscosity Detection - Miao, Wei; Yu, Changjiang; Hao, Erhong; Jiao, Lijuan (Frontiers in Chemistry, 2019)
Abnormal changes of intracellular microviscosity are closely related to many pathologies and diseases. Therefore, monitoring viscosity at cellular and sub-cellular levels is significant for biological research and clinical diagnoses. Fluorescent molecular rotors (FMRs) have recently been developed to detect viscosity, which are characterized by a linear correlation of fluorescence intensity or lifetime to the viscosity of its immediate environment. Recently, 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) derivatives have been widely used to develop FMRs for viscosity probes due to their high rotational ability of the rotor and potentially high brightness. In this minireview, functionalized BODIPYs as FMRs for viscosity detection were collected, analyzed and summarized.